DECOMPOSITION KINETICS AND MECHANISM OF N-HEXADECANE-1,2-13C2 AND DODEC-1-ENE-1,2-13C2 DOPED IN PETROLEUM AND N-HEXADECANE - Burnham A.K.; Gregg H.R.; Ward R.L.; Knauss K.G.; Copenhaver S.A.; Reynolds J.G.; Sanborn R. (My University, 1997)
Isotopically labeled n-hexadecane doped at the percent level in three crude oils is used to determine the intrinsic decomposition kinetics and mechanism of n-alkanes in petroleum. Adjacent 13C labels at the end of the hexadecane and dodecene give a mass fragment sufficiently unique that its disappearance and many of its products can be followed by ordinary gas chromatography-mass spectrometry. Additional structural details of the labeled reaction products are measurable by the NMR INADEQUATE technique, which detects only adjacent 13C atoms. Samples were heated at temperatures ranging from 310 to 360°C in capillary glass tubes and Dickson autoclaves. At temperatures around 350°C, n-alkane decomposition in dissimilar oil matrices forms primarily normal alkanes smaller than the starting alkane at a rate about 60% as fast as the decomposition of the neat alkane. Unlike in neat hexadecane, no significant branched alkanes are formed from the labeled hexadecane in crude oil by alkylation of alkene intermediates. Doping the oils and n-hexadecane with labeled dodecene confirms that alkenes in two of the three oils are rapidly converted primarily to the corresponding alkanes, while reaction of alkenes in hexadecane forms primarily branched alkanes. Reaction of alkenes in the high paraffin oil was intermediate in characteristics. One autoclave experiment included water to assess the importance of water during pyrolysis, with the result that the alkane decomposition rate is affected very little. However, coking of aromatics is inhibited, and there is a significant increase in the production of both H2 and CO2 gas with water present, indicating that water is chemically reactive under these conditions. At temperatures around 310°C, the decomposition rate of neat hexadecane is roughly equal to that in a high paraffin oil and substantially slower than in North Sea and high sulfur oil, suggesting that the effect of the oil matrix has switched from suppression of propagation reactions to enhancement of initiation reactions. The activation energy for doped hexadecane cracking in sealed glass capillaries ranges from about 53 kcal/mol in a North Sea oil to about 62 kcal/mol in high paraffin and high sulfur oils. These values are both lower than for neat hexadecane over the same temperature range but still imply substantial subsurface stability for crude oil.